Mechanical properties and interfacial characteristics of 2.5D SiNOf/BN wave-transparent composites. Issue 10 (August 2019) - Zou, Chunrong; Li, Bin; Liu, Kun; Yang, Xuejin; Li, Duan
Abstract: 2.5D SiNOf /BN wave-transparent composites were fabricated by borazine infiltration and pyrolysis route at 800 °C˜1400 °C. The fracture behavior of the composites was investigated on the basis of the retained fiber strength, in-situ fiber and matrix mechanical properties, and fiber/matrix bonding strength. Nano-indentation were employed to determine the in-situ elastic modulus and hardness of the fiber and BN matrix, and single-fiber push-out experiments were performed to quantify the fiber/matrix bonding strength. The interfacial characteristics of the 800 °C˜1200 °C fabricated composites were further studied in terms of physical bonding and chemical reaction. Physical bonding was resulted from thermal mismatch between the fiber and matrix, which induced compressive radial stress at the interface. The radial stress increased continuously with increasing fabrication temperature. Meanwhile, the TEM analysis confirmed chemical diffusion at the fiber/matrix interface, which further improved the interfacial bonding strength. The chemical reaction mechanism was proposed.